You are on page 1of 3

The Laplacian in Terms of Polar Coordinates

0.1. Linear dierential operators. The Laplacian = x 2 + y 2 + z 2 is an example of a linear dierential operator, which operates on any suciently smooth function u(x, y, z ) placed to the right of it. It is of the second order, in the sense that u only involves derivatives of u of order 2. Given two linear dierential operators L1 and L2 in the same set of variables, they may be added and multiplied according to the rules
2 2 2

(1)

(L1 + L2 )(u) = L1 (u) + L2 (u),

(L1 L2 )(u) = L1 [L2 u],

so the product is the composition of the two operators, whose eect on a function u is to apply rst the right hand factor L2 and then the left hand factor L1 . This multiplication is not commutative, i.e. in general L1 L2 = L2 L1 , but it does obey the associative and distributive laws (2) (L1 L2 )L3 = L1 (L2 L3 ), (L1 + L2 )L3 = L1 L3 + L2 L3 , L1 (L2 + L3 ) = L1 L2 + L1 L3 . Note that the order of a product of two linear dierential operators is the sum of the orders of the two factors. A linear dierential operator of order zero performs no dierentiation at all and just multiplies each function it operates on by some xed function, which it is often convenient to identify with the operator. Thus any smooth function f may be regarded as a linear dierential operator of order 0 dened by f (u) = f u. Lemma 1. Given a smooth function f of n (real) variables x1 , . . . , xn , we have the linear dierential operator identity f (3) f =f + (i = 1, . . . , n). xi xi xi
[Note: The left hand side is the product of the two operators x and f , sometimes written in i the form xi f to avoid misunderstanding, while the second term on the right hand side is the f partial derivative x regarded as a linear dierential operator of order zero.] i Proof. We need only check that both sides of the equation have the same eect on an arbitrary smooth function u(x1 , . . . , un ). This is clear, since the product rule for partial dierentiation yields u f (4) f (u) = (f u) = f + u. xi xi xi xi

Corollary 1. If f is independent of xi , then the linear dierential operators f and

xi

commute.

0.2. The 2D Laplacian in Terms of Plane Polar Coordinates. Since x = r cos , y = r sin , so that r = x2 + y 2 , tan = y/x, the chain rule for partial dierentiation (expressed in operator form) gives r r = + , = + , (5) x x r x y y r y where 1 r r = (2x)(x2 + y 2 )1/2 = x/r = cos , = sin , (6) x 2 y (7) sec2 y sin = 2 = , x x r cos2 sin = , x r 1 1 = = , y x r cos cos = . y r

sec2

Thus sin cos = cos , = sin + , x r r y r r from which we deduce that i i +i = ei + , i = ei , (9) x y r r x y r r where i = 1. Since the linear dierential operators x and y commute, it follows that (8) 2 2 i i (10) + 2 = +i i = ei + ei 2 x y x y x y r r r r Expanding out and using the lemma now gives i i 1 1 i 1 i 1 (11) ei e iei e + iei e + ei e r r r r r r r r 2 2 2 2 1 1 i 1 + + 2 , 2 i i = 2 i 2 r r r r r r r r i.e. 2 2 2 1 1 2 (12) = + = 2+ + . x2 y 2 r r r r2 2 .

0.3. The 3D Laplacian in Terms of Cylindrical Polar Coordinates. It follows immediately from the preceding result that this is 2 1 1 2 2 (13) = 2 + + 2 2+ 2. r r r r z 0.4. The 3D Laplacian in Terms of Spherical Polar Coordinates. These are related to the Cartesian coordinates (x, y, z ) by (14) x = r sin cos , y = r sin sin , z = r cos , r= y . x r = cos , z x2 + y 2 + z 2 ,

(15) Hence (16) (17) Similarly (18) (19) (20) cos sin = ; y r sec2 r x = = sin cos , x r sec2 = x z x

tan =

x2 + y 2 , z

tan =

and similarly =

r = sin sin , y

x2 + y 2

r sin cos cos = , r2 cos sin r cos = z

cos cos = . x r sin = , z r

sec2

x2 + y 2 r sin = 2 , 2 z r cos2 sin = ; x r sin = 0. z

y r sin sin = 2 = 2 2 , x x r sin cos2 1 = , y x cos = ; y r sin

sec2

It follows by the chain rule for partial dierentiation that r cos cos sin (21) = + + = sin cos + , x x r x x r r r sin (22) (23) Hence (24) cos i i = ei sin + x y r r r sin , r cos sin cos = + + = sin sin + + , y y r y y r r r sin r sin = + + = cos . z z r z z r r

so, by the lemma, 2 2 + = +i i 2 2 x y x y x y cos i cos i = ei sin + + ei sin + r r r sin r r r sin 2 2 2 1 1 1 1 = sin2 2 + sin cos 2 i 2 r r r r r r r 2 cos cos (25) + sin + cos + 2 r r r r 2 1 2 i cos cos cos 2 sin 2 r sin sin2 2 2 2 i i cot 1 + i + i + i 2 2 2 2 r r r r r sin 2 2 2 2 2 cos 1 2 sin cos = sin2 2 + + + 2 r r2 2 r2 sin 2 r r 2 1 + cos cot 2 sin cos + + . r r r2 Also 2 sin sin = cos cos 2 z r r r r 2 2 1 1 (26) = cos2 2 cos sin 2 r r r r sin 2 2 sin sin sin 2 + cos cos + 2 r r r r 2 2 2 2 2 sin 2 sin cos sin 2 sin cos + + . = cos2 2 + 2 2 r r r r r r r2 Adding the above two expressions and using the lemma, we nally obtain for the expressions 2 2 1 2 1 2 (27) = + + + cot + r2 r r r2 2 r2 sin2 2 1 2 1 1 2 = 2 r + 2 sin + 2 2 . r r r r sin r sin 2